Vs30 Mapping and Soil Classification in Tiznit Region Based On H/V Spectral Ration Method - Cherki Fadoua; Tadili Mehdi; Tadili Benaissa; Mhammdi Nadia (E3S Web of Conferences)
The average shear wave velocity measured to a depth of 30 meters (VS30) is an important parameter for determining soil characteristics. As part of the seismic risk assessment in the Tiznit region, ambient noise recordings were made during the geophysical investigation campaign using the (H/V) method. The spectral analysis of these recordings enabled the determination of dominant frequencies and the estimation of VS30 values for each site. The aim of this study is to map the spatial variation of VS30 and classify soil types in the Tiznit region. The results show that the soil in the study area is divided into two classes according to the National Earthquake Hazards Reduction Program (NEHRP) classification: Class C refers to soft rock and very dense soils with VS30 greater than 360 m/s, while Class D represents stiff soils with VS30 values between 180 m/s and 360 m/s.